Self-stigma of seeking professional psychological help and its influencing factors among high-risk health care workers for depression and anxiety: a multicenter cross-sectional study - Ruirui Huang; Beimei Lei; Yongrong Liu; Dan Liu; Lijuan Zhang (BMC Psychiatry)
Abstract Objective To investigate the status and influencing factors of self-stigma in seeking professional psychological help among high-risk Chinese Health Care Workers (HCWs) for depression and anxiety. Methods This multicenter survey employed convenience sampling and was conducted from November 2022 to January 2023. A total of 1224 HCWs from 12 hospitals in Hunan Province were selected for an online questionnaire survey. The questionnaire included socio-demographic characteristics of participants, the Self-stigma of Seeking Help Scale, the Perceived Social Support Scale, the Patient Health Questionnaire-9 Scale, the Generalized Anxiety Disorder-7 Scale, and the General Self-Efficacy Scale-Schwarzer. A total score of ≥ 10 on the Patient Health Questionnaire-9 indicated high risk of depression, and a total score of ≥ 10 on the Generalized Anxiety Disorder-7 indicated high risk of anxiety. Data analysis was performed using SPSS 22.0 statistical software. Descriptive statistics, univariate analysis, Spearman correlation analysis, and generalized linear model analysis were used to investigate the status of self-stigma in seeking professional psychological help and to identify its influencing factors among high-risk HCWs. Results Three hundred eighty four valid questionnaires from high-risk HCWs were included in the analysis. The total score of self-stigma of seeking professional psychological help among high-risk Chinese HCWs was 30.0 (26.0, 30.0). Results from the generalized linear model showed that average daily sleep duration, social support, depressive symptoms, and anxiety symptoms were significant influencing factors of self-stigma in seeking professional psychological help (all P < 0.05). Conclusion The level of self-stigma of seeking professional psychological help among high-risk HCWs was moderate level, and diverse factors contribute to the self-stigma of seeking professional psychological help. Our study could inform the development of appropriate interventions to reduce self-stigma in seeking professional psychological help and enhance mental health among high-risk HCWs.